1999
DOI: 10.1086/501655
|View full text |Cite
|
Sign up to set email alerts
|

Screening High-Risk Patients for Methicillin-ResistantStaphylococcus Aureuson Admission to the Hospital Is It Cost Effective?

Abstract: If early identification of MRSA in colonized patients prevents nosocomial transmission of the organism to as few as six new patients, the screening program would save money.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
1
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(137 citation statements)
references
References 18 publications
5
121
1
8
Order By: Relevance
“…Hospital infection control is costly and despite some evidence suggesting infection-related costs exceed those of screening and control [4,[21][22][23], the costs and benefits associated with screening are largely unknown. This may lead to reservations regarding strategy implementation and so a greater understanding of the potential benefits and pitfalls is clearly needed.…”
Section: Choosing a Screening Strategymentioning
confidence: 99%
“…Hospital infection control is costly and despite some evidence suggesting infection-related costs exceed those of screening and control [4,[21][22][23], the costs and benefits associated with screening are largely unknown. This may lead to reservations regarding strategy implementation and so a greater understanding of the potential benefits and pitfalls is clearly needed.…”
Section: Choosing a Screening Strategymentioning
confidence: 99%
“…Long-term catheters that are implemented to administer chemotherapy predispose patients to MRSA bacteremia and catheter infections. Patients who are admitted from health care facilities or nursing homes should be screened for MRSA colonization [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Calfee et al (2002) 40 estimated that the reduction in MRSA bacteremia as a result of active surveillance and isolation measures is associated with a saving of US$313,596 to $975,632 for one hospital over one year. Papia et al 42 demonstrated that early identification of six or more new MRSA-colonized patients, and the consequent decrease in transmission, makes the active surveillance program cost-effective. Karchmer et al 43 estimated that the cost of active surveillance and isolation of patients colonized and infected by MRSA was 19-27 times lower than that attributable to MRSA bacteremia as a result of an uncontrolled outbreak.…”
Section: Active Surveillance Of Colonization For Patientsmentioning
confidence: 99%